Joseph Kosuth: Análise de uma teoria para a arte - Fernanda Pereira Medina (2007)
This research is based on Joseph Kosuth writings. He is an American plastic artist and is considered one of the most influent in the contemporary art movement, known as Conceptual Art. Among all of the conceptual artists, he was one who most dedicated his thoughts to the construction of consistent theoretical bases to the delimitation of this movement. He proposed new challenges to artists, public and critics in the end of 60s and beginning of the 70s. In his most controversial thesis, published in the text Art after Philosophy, in 1969, he states that the 20th century watches the death of philosophy and the birth of art. He defends a thought line which denies the aesthetic dimension of the art, in order to justify linguistically the art propositions. His arguments are based on the thoughts of some analytical philosophers and on the linguistic theory of Ludwig Wittgenstein. The discussions sent by Kosuth go straightly against the artistic conventions postulated on Modernism and the corresponding criticism, especially Clement Greenberg, the modernist critic for excellence. The guide line of this work discusses the relation between the Conceptual Art and the Kantian aesthetic, along with the Wittgenstein linguistic theory and the ways Greenberg would establish for the art.